Population genetics of cucumber mosaic virus infecting medicinal, aromatic and ornamental plants from northern Italy - Davino, Salvatore; Panno, Stefano; Rangel, Ezequiel A.; Davino, Mario; Bellardi, Maria Grazia; Rubio, Luis (2017)
The genetic variation and evolution of cucumber mosaic virus (CMV) from aromatic, medicinal and ornamental plants in northern Italy was studied by sequence analysis of the movement protein gene and comparison with equivalent sequences of isolates from other countries. Comparison of nonsynonymous and synonymous substitutions suggested that 30% of amino acid sites were under negative selection and only one was under positive selection. Phylogenetic, nucleotide diversity and genetic differentiation analyses suggested that long-distance migration plays a role in the evolution and determination of the genetic structure and diversity of CMV in northern Italy and other areas.